SMALL-SCALE STRUCTURE OF LITHOSPHERE-ASTHENOSPHERE BENEATH GAURIBIDANUR SEISMIC ARRAY DEDUCED FROM AMPLITUDE AND PHASE FLUCTUATIONS - Tripathi J.N. (My University, 2001)
The cross coherence function between log amplitude and phase (or travel time) has been analyzed along with the transverse coherence functions of log amplitude and phase in order to estimate the statistical dis-tribution of heterogeneities beneath the Gauribidanur Seismic array (GBA). The power spectra of the P-wave velocity variations can be estimated under the array with the help of the transverse coherence func-tions (TCFs). The data of 72 earthquakes have been used to calculate the three TCFs (of phase, log amplitude and cross-coherence). The central frequency is 2 Hz. The measured root mean square (rms) log amplitude fluctuation is 0.40 and the rms phase fluctuation is 0.88. An overlapping two-layer model has been obtained for lithosphere and asthenosphere heterogeneities beneath GBA with different power law spectra. The upper layer, in which the heterogeneities are defined by Gaussian correlation function extends from the surface to about 160 km depth while the lower layer, in which the heterogeneities are defined by exponential correlation function extends from 16 to 280 km. The rms P-wave velocity variation has been estimated in the range of 0.3–1.5%. Clustering of cracks or intrusions may be responsible for the small-scale heterogeneities while temperature or compositional heterogeneities may be the cause of large-scale wave heterogeneities.